Modular Access to P(V)‐Stereogenic Compounds via Cu‐Catalyzed Desymmetrization of (Thio)Phosphonic Dichlorides - Yao, Hong‐Qing; Cai, Yue‐Ming; Xie, Tian; Lv, Ji‐Yuan; Fang, Shuai‐Shuai; Li, Ming‐Hong; Shang, Ming (Angewandte Chemie International Edition, 2025)
Chiral phosphorus(V) centers—particularly those bearing fully heteroatom‐substituted frameworks—are key stereochemical motifs in pharmaceuticals, nucleic acid therapeutics, and functional materials. However, their stereoselective construction remains a long‐standing challenge in synthetic chemistry. Here, we report a copper‐catalyzed desymmetrization strategy enabled by rationally engineered PIM ligands that affords broad and modular access to structurally diverse P(V)‐stereogenic compounds. By harnessing the tunable Lewis acidity and well‐defined chiral environment of the catalyst—together with the distinct mechanistic features of chiral Lewis acid catalysis—this strategy overcomes the substrate scope limitations that have constrained traditional approaches. The method demonstrates broad functional group tolerance and delivers high levels of stereocontrol across seven distinct substitution patterns, including the efficient construction of chiral P═S motifs previously considered synthetically challenging. Importantly, the approach enables efficient late‐stage derivatization of nucleosides and their analogs, thereby providing a general entry point to stereodefined P(V)‐containing bioactive molecules. This work not only expands the utility of transition‐metal Lewis acid catalysis in phosphorus chemistry, but also establishes a versatile framework for applications in drug discovery and nucleic acid‐based therapeutics where precise stereochemical control is essential. A Cu‐catalyzed desymmetrization strategy using newly modified chiral PIM ligands enables modular access to diverse P(V)‐stereogenic compounds with high stereocontrol. This approach tolerates broad functionality, constructs challenging P═S motifs, and enables late‐stage nucleoside derivatization, providing a versatile platform for drug and nucleic acid‐based therapeutic development.